A 85-dB dynamic range multibit delta-sigma ADC for ADSL-CO applications in 0.18-μm CMOS. - Gaggl, R. (IEEE Journal of solid state circuits)
A high-resolution multibit sigma-delta analog-to-digital converter (ADC) implemented in a 0.18-μm CMOS technology is introduced. The circuit is targeted for an asymmetrical digital subscriber line (ADSL) central-office (CO) application . An area- and power-efficient realization of a second-order single-loop 3-bit modulator with an oversampling ratio of 96 is presented. The ΣΔ modulator features an 85-dB dynamic range over a 300-kHz signal bandwidth. The measured power consumption of the ADC core is only 15 mW. An innovative biasing circuitry is introduced for the switched-capacitor integrators.